Дослідження процесів у перетворювачі з чотиризонним регулюванням напруги і електромеханічним навантаженням - Михайленко, Владислав Володимирович; Святненко, В. А.; Чуняк, Ю. М.; Бачинський, В. І. (Національний технічний університет "Харківський політехнічний інститут", 2021)
Розроблено нові математичні моделі електромагнітних процесів у трифазних електричних колах напівпровідникових перетворювачів з багатоканальним зонним регулюванням фазних напруг без урахування енергетичних втрат у напівпровідникових комутаторах для швидкої оцінки впливу параметрів навантаження на рівень і форму вихідної напруги. У цій статті проведено аналіз електромагнітних процесів в електричних колах напівпровідниковими з комутаторами. Створено математичну модель для аналізу електромагнітних процесів в напівпровідникових перетворювачах з широтно-імпульсним регулюванням вихідної напруги. Наведено графіки, що від ображають електромагнітні процеси у електричних колах. Стаття присвячена розвитку метода багатопараметричних функцій шляхом розробки нових математичних моделей та визначення функцій і алгоритмічних рівнянь для аналізу за підсистемними складовими електромагнітних процесів у розгалужених електричних колах з напівпровідниковими комутаторами і ланками з синусоїдальними, постійними і імпульсними напругами. Напівпровідникові комутатори можуть виконувати високочастотне змінення структури електричних кіл і широтно-імпульсну модуляцію фазних і лінійних напруг трифазної мережі електроживлення, виконуючи регулювання вихідних напруг напівпровідникових перетворювачів параметрів електричної енергії.

The new mathematical models of the electromagnetic processes is designed in three-phase electric circuit of the semiconductor converters with many-server zoned regulation phases voltages disregarding losses in semiconductor commutator for quick estimation of the influence parameter loads on level and form of the output voltage. mathematical model of the semiconductor converter is also used for study of the connecting processes in semiconductor converter with actively-inductive load. Will develop the method multivariable function, what fall into algorithmic equations of the analysis formed and connecting processes in furcated electric circuit with semiconductor commutator and reactive element, toward accou nt of the particularities of the use phase and linear voltages to network of the power supply. Analysis of the electromagnetic processes is organized beside this article in electric circuit with semiconductor commutator. Mathematical model is created for analysis electro-magnetic processes in semiconductor converter with width pulsed regulation of the output voltage. The broughted graphs, which reflect the electromagnetic processes in electric circuit. Method much parametric functions was used when performing calculation. The mathematical model of the converter is created for eleven zoned regulations of the output voltage. Article is devoted to the development of a method of multi-parametric modulating functions by means of working out of new mathematical models and definition of functions and the algorithmic equations for the analysis on sub-system components of electromagnetic processes in electric circuits of variable structure with sinusoidal, direct and pulsing voltage. Introduction of functions with discrete parameters in the algorithmic equations for analysis of processes in circuits with semiconductor commutators simplifies modeling on subsystem components. The mathematical model of steady-state processes and transients in electric circuits of semiconductor converters of modulation type with multi-channel zonal use of phase and line voltages of a three-phase network of power supplies is developed. The mathematical model of electric circuits of thyristor shapers of electrodischarge pulses for the analysis and the matching of capacitors charging modes with decrease several times of electric resistance of technological load is also created.
Research of processes in a converter with four-zone voltage regulation and electromechanical load
Keywords: електромагнітні процеси; вихідні напруга та струм; двигун постійного струму; метод багатопараметричних модулюючих функцій; electromagnetic processes; the output voltage and current; the engine of the direct current; method multivariable modulating function